A study on nanostructured of anodised aluminium template synthesised by the mixture of phosphoric acid and acetic acid - Juyana A.Wahab (School of Materials Engineering, University Malaysia Perlis, 2010)
This study was performed to determine optimum parameter of anodising process in order to develop AAO film with diverse application in electronic field. The studies were focused on the influence of anodising parameters which are anodising temperature and anodising voltage on the growth of AAO film.